The outsourcing decision-making process: two extensions to the management accounting toolkit - Nielsen, Lars Bråd; Nørreklit, Hanne (Proceedings of Pragmatic Constructivism, 2012)
In response to a lack of research, this paper explores the type of reasoning that companies use to structure their complex outsourcing decision and the procedures for producing relevant accounting information. Analyzing two manufacturing companies, we uncover two methods for structuring the outsourcing decision-making process and for determining relevant accounting information: an analytical method and an actor-based method rooted in pragmatic constructivism. The two cases show that both strategy and management accounting play an interrelated, crucial role in the decision to outsource. The article adds to the academic literature on calculative decision theory by accentuating the notion of ‘practice’ rational decision-making, where managers have to integrate sensing and reasoning into practical affairs. In practice, the results provide extensions to the management accounting toolkit since these cases can serve as inspiration for structuring the outsourcing decision-making process in similar situations.